Situational Crime Prevention at Specific Locations in Community Context: Place and Neighborhood Effects in Cincinnati, Ohio, 2005-2008 - Eck, John ([Verlag nicht ermittelbar], 2013)
The study examined the situational and contextual influences on violence in bars and apartment complexes in Cincinnati, Ohio. Interviews of managers and observations of sites were made for 199 bars (Part 1). Data were collected on 1,451 apartment complexes (Part 2). For apartment complexes owners were interviewed for 307 and observations were made at 994. Crime data were obtained from the Cincinnati Police Department records of calls for service and reported crimes.